Radio contact in high-rises can quit on firefighters. - Goldstein, H.
During the crucial minutes when firefighters needed them most, the handheld radios used by the Fire Department of the City of New York (FDNY) at the World Trade Center (WTC) on 11 September did not work. This illustrated that wireless communication in skyscrapers is an unsolved and dangerous problem. Could ultrawideband offer solutions? UWB contrasts sharply with conventional radio systems such as personal communications services (PCS), which emit a bit of power in their own narrow portion of the spectrum (1.85-1.99 GHz). Instead of modulating a single sinusoidal wave to transmit voice and data, UWB transmits a train of pulses in which variations in the intervals between the pulses carry information. The pulses are very low power, from a few milliwatts down to about 50 pW, and are transmitted at very high speed, in millions to billions per second, which spreads them over a very wide frequency band, resulting in high resolution and low frequencies
Keywords: 1.85 to 1.99 GHz; City of New York; PCS; September 11.; UHF; UWB; World Trade Center; Firefighters; Personal communications services; Radio systems; Skyscrapers; Ultrawideband communications; Wireless communication